El diablo de la ficción. Cuento etnográfico - Sánchez Pérez, Francisco (Revista de Antropología Social, 2008)
This paper takes up the theme of fiction as an epistemological problem of anthropological knowledge. To do so, the author doesn’t use the essay, a means of expression that is canonically accepted in the discipline of anthropology, but he offers us a short story, the argument of which suggests, in turn, that fiction is a part of the process of writing the ethnographic text
Keywords: Fiction; Realism; Imagination; Orthodoxy; Creation; Strategy of narrative; Representation; Anthropological novel